Differential Effects of ‘Vaping’ on Lipid and Glucose Profiles and Liver Metabolic Markers in Obese Versus Non-obese Mice - Chen, Hui; Li, Gerard; Chan, Yik Lung; Zhang, Hui Emma; Gorrell, Mark D.; Pollock, Carol A.; Saad, Sonia; Oliver, Brian G. (Frontiers in Physiology, 2021)
Tobacco smoking increases the risk of metabolic disorders due to the combination of harmful chemicals, whereas pure nicotine can improve glucose tolerance. E-cigarette vapour contains nicotine and some of the harmful chemicals found in cigarette smoke at lower levels. To investigate how e-vapour affects metabolic profiles, male Balb/c mice were exposed to a high-fat diet (HFD, 43% fat, 20kJ/g) for 16weeks, and e-vapour in the last 6weeks. HFD alone doubled fat mass and caused dyslipidaemia and glucose intolerance. E-vapour reduced fat mass in HFD-fed mice; only nicotine-containing e-vapour improved glucose tolerance. In chow-fed mice, e-vapour increased lipid content in both blood and liver. Changes in liver metabolic markers may be adaptive responses rather than causal. Future studies can investigate how e-vapour differentially affects metabolic profiles with different diets.